2021
DOI: 10.1186/s12864-021-07452-1
|View full text |Cite
|
Sign up to set email alerts
|

Antennal transcriptome analysis of olfactory genes and characterizations of odorant binding proteins in two woodwasps, Sirex noctilio and Sirex nitobei (Hymenoptera: Siricidae)

Abstract: Background The woodwasp Sirex noctilio Fabricius is a major quarantine pest worldwide that was first discovered in China in 2013 and mainly harms Pinus sylvestris var. mongolica Litv.. S. nitobei Matsumura is a native species in China and is closely related to S. noctilio. Recently, the two woodwasps species were found attacking the P. sylvestris var. mongolica Litv in succession. The olfactory system is the foundation of insect behavior. Olfactory genes were identified through antennal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…The olfactory system of insects is important to the completion of host positioning, feeding, mating, oviposition, and other behaviors [ 1 , 2 ]. Insects can perceive the information of odor molecules in the external environment and respond accordingly [ 3 ], and primarily rely on the antennae, a primary chemical sensory organ with various sensilla [ 4 ]. In general, the olfactory system mainly involves several gene families: odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs), ionotropic receptors (IRs) and sensory neuron membrane proteins (SNMPs), which mainly locate on the sensilla to process various odorants or pheromones and elicit related behaviors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory system of insects is important to the completion of host positioning, feeding, mating, oviposition, and other behaviors [ 1 , 2 ]. Insects can perceive the information of odor molecules in the external environment and respond accordingly [ 3 ], and primarily rely on the antennae, a primary chemical sensory organ with various sensilla [ 4 ]. In general, the olfactory system mainly involves several gene families: odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs), ionotropic receptors (IRs) and sensory neuron membrane proteins (SNMPs), which mainly locate on the sensilla to process various odorants or pheromones and elicit related behaviors [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that Minus-C OBPs originated from a Classic OBP that lost two cysteine residues during evolution, rather than having evolved from a Minus-C OBP of another species [ 56 ]. The Plus-C and Minus-C subfamilies play different roles in different biological processes [ 57 59 ]. PBPs are a branch of Classic OBPs known for high levels of expression in Lepidopteran male antennae, and it has been reported that many insect PBPs can bind pheromones [ 52 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qPCR experiment demonstrated that SnocOBP9 was abundantly expressed in both male and female antennae. These results indicate that SnocOBP9 may be involved in the process of chemoreception in insects [ 56 ]. However, it has not been determined whether SnocOBP9 possesses olfactory functions, and the mechanisms underlying the interactions between SnocOBP9 and ligands are also unclear [ 57 ].…”
Section: Introductionmentioning
confidence: 99%